Hindgut Innate Immunity and Regulation of Fecal Microbiota through Melanization in Insects - Shao, Qimiao (American Society for Biochemistry and Molecular Biology, 2012)
Many insects eat the green leaves of plants but excrete black feces in an as yet unknown mechanism. Insects cannot avoid ingesting pathogens with food that will be specifically detected by the midgut immune system. However, just as in mammals, many pathogens can still escape the insect midgut immune system and arrive in the hindgut, where they are excreted out with the feces. Here we show that the melanization of hindgut content induced by prophenoloxidase, a key enzyme that induces the production of melanin around invaders and at wound sites, is the last line of immune defense to clear bacteria before feces excretion. We used the silkworm Bombyx mori as a model and found that prophenoloxidase produced by hindgut cells is secreted into the hindgut contents. Several experiments were done to clearly demonstrate that the blackening of the insect feces was due to activated phenoloxidase, which served to regulate the number of bacteria in the hindgut. Our analysis of the silkworm hindgut prophenoloxidase discloses the natural secret of why the phytophagous insect feces is black and provides insight into hindgut innate immunity, which is still rather unclear in mammals.